2005
DOI: 10.1021/jf048701t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roasting on the Formation of Chlorogenic Acid Lactones in Coffee

Abstract: Of all plant constituents, coffee has one of the highest concentrations of chlorogenic acids. When roasting coffee, some of these are transformed into chlorogenic acid lactones (CGL). We have studied the formation of CGL during the roasting of coffee beans in Coffea arabica cv. Bourbon; C. arabicacv. Longberry; and C. canephora cv. Robusta. Individual CGL levels were determined by comparison of HPLC peaks with those of synthetic CGL standards. Seven CGL were identified: 3-caffeoylquinic-1,5-lactone (3-CQL), 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
406
2
32

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 467 publications
(488 citation statements)
references
References 28 publications
48
406
2
32
Order By: Relevance
“…It was observed that when comparing the concentration of phenolic compounds in green coffee grains and in dark roasts, there was a linear decrease in total phenolic compounds (Sacchetti et al, 2009). Farah et al (2005) reported that some phenolic compounds present in coffee, such as chlorogenic acids, are degraded into low molecular weight compounds through the roasting process and are partly transformed into quinolactones due to dehydration and the formation of intermolecular bonds.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that when comparing the concentration of phenolic compounds in green coffee grains and in dark roasts, there was a linear decrease in total phenolic compounds (Sacchetti et al, 2009). Farah et al (2005) reported that some phenolic compounds present in coffee, such as chlorogenic acids, are degraded into low molecular weight compounds through the roasting process and are partly transformed into quinolactones due to dehydration and the formation of intermolecular bonds.…”
Section: Resultsmentioning
confidence: 99%
“…However, the total CGA content of green coffee beans may vary not only according to genetics-species but also to the degree of maturation, agricultural practices, climate and soil [16,17]. For example CGA content found in different coffee species of wild Coffea genetic resources varies between 0.61 and 1.05 % for Coffea sp.…”
Section: Phenolic Acids and Lactonesmentioning
confidence: 99%
“…During roasting, a part of CGA is isomerized, a part is transformed into quinolactones due to dehydration and formation of an intramolecular bond, and a part is hydrolyzed and degraded into low molecular weight compounds or even reduced [12,13,16]. It depends on parameters of roasting process and coffee preparing [33][34][35].…”
Section: Phenolic Acids and Lactonesmentioning
confidence: 99%
“…Pure reference standards of 5-caffeoylquinic acid (5-CQA) and caffeine were obtained from Sigma-Aldrich (Steinheim, Germany) and pure reference standards of 3,4-, 3,5-and 4,5-dicaffeoylquinic acids were purchased from Phytolab (Vestenbergsgreuth, Germany). A mixture of 3-CQA, 4-CQA, and 5-CQA was prepared from 5-CQA using the isomerization method of Trugo & Macrae, 20 also described in Farah et al 21 …”
Section: Chemicals and Reagentsmentioning
confidence: 99%